The Contribution of Crop Residues in Sustainable Production of Maize and Groundnut in a Crop Rotation System - Abdalla, Mubarak AbdelRahman (2000)
Field and laboratory experiments were carried out with the main objective of studying the contribution of crop residues in sustaining yields of maize (Zea mays L.) and groundnut (Arachis hypogaea) in a crop rotation system under Malaysian tropical conditions. Five cropping seasons of a rotation of sweet com - groundnut - sweet com - ground nut - sweet com was conducted with three treatments (i) recommended inorganic fertilizer with crop residues (T1), (ii) recommended inorganic fertilizer without crop residues (T2) and (iii) combination of inorganic fertilizer and chicken manure (10 tha -I) with crop residues (T3). The 15N tracing technique was used to study the fate of applied inorganic fertilizer, (15NH4)2SO4 , in Tl and T2 treatments. All the plots were limed at 2 tha-I before sowing each crop. Two secondary experiments were carried out in the main field experiment to (i) investigate nutrient release from decomposing 15N-labelled maize stover and N uptake by the subsequent groundnut crop using mineralization tubes and (ii) to compare the decomposition rates and nutrient release patterns of maize and groundnut residues using litterbags. Also, two incubation studies were conducted in the laboratory, first, to determine potential N mineralization rates from above and below ground crop residues and second to determine potential N - mineralization rates of maize stover and groundnut haulm in selected five Malaysian soil series.